Recollections of an economist - KALDOR, N. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it Nicholas Kaldor describes how he came to be an economist and his subsequent intellectual development. JEL: B31